Having the knowledge of the Formulae is a prerequisite here.

Example 1 of Solving Logarithms :

Express the following as single logarithms to any base. (i) (1⁄2) log (a + b) - (1⁄2) log (a - b) (ii) log (a + b) + log (a^{2} - ab + b^{2}) - log (x - y) - log (x^{2} + xy + y^{2}) (iii) (3⁄2) log x - (1⁄3) log y + (2⁄3) log z - (1⁄5) log a

Solution to Example 1 of Solving Logarithms :

Solution to 1(i) of Solving Logarithms :

Let P = (1⁄2) log (a + b) - (1⁄2) log (a - b) We know in log of a power (see Formula 7) , the exponent multipliesthe log. Considering the reverse, If a quantity multiplies thelog, it becomes exponent. ∴ P = log {(a + b)^{(1⁄2)}} - log {(a - b)^{(1⁄2)}} We know, log of a quotient can be written as the difference of the logs of the numerator and denominator of the quotient (See Formula 6) Considering the reverse, the difference of the logs of different quantitiescan be written as log of a quotient (the quantity whose log has negative sign, in the denominator) of the quantities. = log {(a + b)^{(1⁄2)}}⁄{(a - b)^{(1⁄2)}} = log {(a + b)⁄(a - b)}^{(1⁄2)}. Ans.

Solution to 1(ii) of Solving Logarithms :

Let P = log (a + b) + log (a^{2} - ab + b^{2}) - log (x - y) - log (x^{2} + xy + y^{2}) = log (a + b) + log (a^{2} - ab + b^{2}) - {log (x - y) + log (x^{2} + xy + y^{2})} We know, log of a product can be written as the sum of the logs of the factors of the product (See Formula 5) Considering the reverse, the sum of the logs of different quantitiescan be written as log of product of the quantities. ∴ P = log {(a + b)(a^{2} - ab + b^{2})} - log {(x - y)(x^{2} + xy + y^{2})} We know from Polynomials, (a + b)(a^{2} - ab + b^{2}) = a^{3} + b^{3}; and (x - y)(x^{2} + xy + y^{2}) = x^{3} - y^{3} ∴ P = log (a^{3} + b^{3}) - log (x^{3} - y^{3}) We know, log of a quotient can be written as the difference of the logs of the numerator and denominator of the quotient (See Formula 6) Considering the reverse, the difference of the logs of different quantitiescan be written as log of a quotient (the quantity whose log has negative sign, in the denominator) of the quantities. ∴ P= log {(a^{3} + b^{3})⁄(x^{3} - y^{3})} Ans.

Solution to 1(iii) of Solving Logarithms :

Let P = (3⁄2) log x - (1⁄3) log y + (2⁄3) log z - (1⁄5) log a We know in log of a power (see Formula 7) , the exponent multipliesthe log. Considering the reverse, If a quantity multiplies thelog, it becomes exponent. ∴ P = log x^{(3⁄2)} + log z^{(2⁄3)} - {log y^{(1⁄3)} + log a^{(1⁄5)}} We know, log of a product can be written as the sum of the logs of the factors of the product (See Formula 5) Considering the reverse, the sum of the logs of different quantitiescan be written as log of product of the quantities. ∴ P = log {x^{(3⁄2)} x z^{(2⁄3)}} - log {y^{(1⁄3)} x a^{(1⁄5)}} We know, log of a quotient can be written as the difference of the logs of the numerator and denominator of the quotient (See Formula 6) Considering the reverse, the difference of the logs of different quantitiescan be written as log of a quotient (the quantity whose log has negative sign, in the denominator) of the quantities. ∴ P = log [{x^{(3⁄2)} x z^{(2⁄3)}}⁄{y^{(1⁄3)} x a^{(1⁄5)}}] Ans.

Get The Best Grades With the Least Amount of Effort

Here is a collection of proven tips, tools and techniques to turn you into a super-achiever - even if you've never thought of yourself as a "gifted" student.

The secrets will help you absorb, digest and remember large chunks of information quickly and easily so you get the best grades with the least amount of effort.

If you apply what you read from the above collection, you can achieve best grades without giving up your fun, such as TV, surfing the net, playing video games or going out with friends!

3^{(2x + 1)}.4^{(4x - 1)} = 36 Taking logarithms on both sides, we get log {3^{(2x + 1)}.4^{(4x - 1)}} = log 36 ⇒ log {3^{(2x + 1)}} + log {4^{(4x - 1)}} = log 36 We know in log of a power (see Formula 7) , the exponent multipliesthe log. ∴ (2x + 1) log 3 + (4x - 1) log 4 = log 36 ⇒ 2x log 3 + 4x log 4 + log 3 - log 4 = log 36 ⇒ 2x(log 3 + 2 log 4) = log 36 - log 3 + log 4 We know in log of a power (see Formula 7) , the exponent multipliesthe log. Considering the reverse, If a quantity multiplies thelog, it becomes exponent. ∴ L.H.S. = 2x(log 3 + log 4^{2}) We know, log of a product can be written as the sum of the logs of the factors of the product (See Formula 5) Considering the reverse, the sum of the logs of different quantitiescan be written as log of product of the quantities. We know, log of a quotient can be written as the difference of the logs of the numerator and denominator of the quotient (See Formula 6) Considering the reverse, the difference of the logs of different quantitiescan be written as log of a quotient (the quantity whose log has negative sign, in the denominator) of the quantities. Applying these to L.H.S. and R.H.S., we get 2x{log (3 x 4^{2})} = log (36 x 4⁄3) = log 48 ⇒ 2x{log 48} = log 48 ⇒ 2x = 1 ⇒ x = 1⁄2. Ans.

Alternative Solution: This problem can be solved from Exponents knowledge without using logarithms as given below. 3^{(2x + 1)}.4^{(4x - 1)} = 36 ⇒ 3^{(2x)}.3^{1}.4^{(4x)}.4^{(-1)} = 36 ⇒ (3)^{2x}.(4^{2})^{2x}.(3⁄4) = 36 ⇒ 3^{2x}.(16)^{2x} = 36 x (4⁄3) = 48 ⇒ (3 x 16)^{2x} = 48 ⇒ (48)^{2x} = 48 ⇒ 2x = 1 ⇒ x = 1⁄2. Ans.

Solution to 2(ii) of Solving Logarithms :

The given equation is 4^{(log9 3)} + 9^{(log2 4)} = 10^{(logx 83)} We have log_{9} 3 = log_{32} 3^{1} We know, in log of a power to the base of another power (see Formula 9),the quotient of the exponents (exponent of the base in the denominator) multiplies the log. ∴ log_{9} 3 = (1⁄2) log_{3} 3 We know log of a quantity to the same base is 1. (See Formula 4) ∴ log_{9} 3 = (1⁄2) (1) = 1⁄2; log_{2} 4 = log_{2} 2^{2} We know in log of a power (see Formula 7) , the exponent multipliesthe log. ∴ log_{2} 4 = 2 log_{2} 2 We know log of a quantity to the same base is 1. (See Formula 4) ∴ log_{2} 4 = 2 (1) = 2 ∴ the given equation becomes 4^{(1⁄2)} + 9^{2} = 10^{(logx 83)} ⇒ 2 + 81 = 10^{(logx 83)} ⇒ 83 = 10^{(logx 83)} .......(i) By converting the exponential form of (i) to logarithmic form (See Formula 1), we get log_{x} 83 = log_{10} 83 When two logarithms of same quantities are equal, their bases have to be equal. ∴ x = 10. Ans. You can also apply Formula 2 to equation (i), to conclude x = 10.Ans.

More Solved Examples : Solving Logarithms

The following Link takes you to more Solved Examples.

Are you spending lot of money for math tutors to your child and still not satisfied with his/her grades ?

Do you feel that more time from the tutor and more personalized Math Help to identify and fix the problems faced by your child will help ?

Here is a fool proof solution I strongly recommend and that too With a minuscule fraction of the amount you spent on tutors with unconditional 100% money back Guarantee, if you are not satisfied.

It is like having an unlimited time from an excellent Tutor.

It is an Internet-based math tutoring software program that identifies exactly where your child needs help and then creates a personal instruction plan tailored to your child’s specific needs.

If your child can use a computer and access the Internet, he or she can use the program. And your child can access the program anytime from any computer with Internet access.

There is an exclusive, Parent Information Page provides YOU with detailed reports of your child’s progress so you can monitor your child’s success and give them encouragement. These Reports include

Time spent using the program

Assessment results

Personalized remediation curriculum designed for your child

Details the areas of weakness where your child needs additional help

Provides the REASONS WHY your child missed a concept

List of modules accessed and amount of time spent in each module

Quiz results

Creates reports that can be printed and used to discuss issues with your child’s teachers

These reports are created and stored in a secure section of the program, available exclusively to you, the parent. The section is accessed by a password that YOU create and use. No unauthorized users can access this information.

Its research-based results have proven that it really works for all students! in improving math skills and a TWO LETTER GRADE INCREASE in math test scores!,if they invest time in using the program.

Proven for More than 10,000 U.S. public school students who increased their math scores.

Solve the following problems on Solving Logarithms

Solve 4^{x} + 2^{(2x - 1)} = 3^{(x + 1⁄2)} + 3^{(x - 1⁄2)} (i) by using logarithms (ii) without using logarithms.

If (log_{y}x.log_{z}x - log_{x}x) + (log_{z}y.log_{x}y - log_{y}y) + (log_{x}z.log_{y}z - log_{z}z) = 0, prove that xyz = 1.

For Answer to problem1 of the above exercise on Solving Logarithms see at the bottom of the page.

Progressive Learning of Math : Solving Logarithms

Recently, I have found a series of math curricula (Both Hard Copy and Digital Copy) developed by a Lady Teacher who taught everyone from Pre-K students to doctoral students and who is a Ph.D. in Mathematics Education.

This series is very different and advantageous over many of the traditional books available. These give students tools that other books do not. Other books just give practice. These teach students “tricks” and new ways to think.

These build a student’s new knowledge of concepts from their existing knowledge. These provide many pages of practice that gradually increases in difficulty and provide constant review.

These also provide teachers and parents with lessons on how to work with the child on the concepts.

The series is low to reasonably priced and include